Peningkatan Minat Baca, Kesadaran Pendidikan, Dan Nilai Keagamaan Di Dusun Sidorejo - Nur Hakim, Syahrul Erfiansyah; Caroline, Diva Azalia; Azzuhdi, Abdurrohman Naufal; Halimah, Husnun; Azhari, Arina Fadhilah; Febrianti, Yossi Candra; Haryanti, Siska; Fauzi, Ilham; Ardiansyach, Bagoes; Muzakka, Zhafif Almas; Kartika, Wisnu (Prosiding Seminar Nasional Program Pengabdian Masyarakat, 2025)
The Community Service Program (PKM) in Sidorejo Hamlet was carried out to address various community issues, such as the low reading interest among children, lack of environmental awareness, and the prevalence of bullying in schools. This program adopted a participatory and collaborative approach, actively involving community members in every activity implemented. The programs conducted included the Literacy Corner to enhance reading interest, tutoring sessions to support academic achievement, socialization of modern farming techniques for local farmers, and an anti-bullying campaign in schools. The outcomes of these activities showed an increase in children's reading interest and academic development among tutoring participants. Overall, the PKM 052 program provided direct benefits to the community and successfully fostered active participation in improving the quality of education in Sidorejo Hamlet